Design and Implementation for 3-DoF SCARA Robot based PLC - Karem, Iman Salih; A.Wahabt, Talal A. Jabbar; Yahyh, Mawadah Jlaa (Al-Khwarizmi Engineering Journal, 2017)
Abstract This paper presents mechanical and electrical design, and implementation  process of industrial robot, 3-DoF type SCARA (selective compliment assembly robot arm),with two rotations and one translation used for welding applications.The design process also included the controller design which was based on PLC(programmable logic controller) as well as selection of mechanical and electrical components.The challenge was to use the available components in Iraq with reasonable costs. The robot mentioned is fully automated using programmable logic controller PLC(Zelio type SR3-B261BD),with 16inputs and 10 outputs. The PLC was implemented in FBD logic to obtain three different automatic motions with high efficiency withouterror,where the two links can stop in a certain points and link 3 bushed down for doing the task in a desired trajectory motion by programming the PLCcontroller.Keywords: DoF, FBD, PLC, SCARArobot.